2016
DOI: 10.1007/s00221-016-4735-0
|View full text |Cite
|
Sign up to set email alerts
|

Representational pseudoneglect for detecting changes to Rey–Osterrieth figures

Abstract: When dividing attention between the left and right sides of physical space, most individuals pay slightly more attention to the left side. This phenomenon, known as pseudoneglect, may also occur for the left and right sides of mental representations of stimuli. Representational pseudoneglect has been shown for the recall of real-world scenes and for simple, briefly presented stimuli. The current study sought to investigate the effect of exposure duration and complexity using adaptations of the Rey-Osterrieth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…Our findings using object-like abstract shapes are in stark contrast to the findings of Pia et al (2010) and previous work (Aniulis et al, 2016; Churches et al, 2017) using semantically unengaging geometric shapes (circle, rectangle, triangle, Rey-Osterrieth complex figures).These studies revealed consistent, and frequently significant, evidence of a leftward bisection bias. Pia et al (2010) asked participants to bisect a line drawing image of a basset-hound stretched so it resembled two parallel line stimuli with meaningful information at either end.…”
Section: Interim Discussion—experiments 1 Andcontrasting
confidence: 99%
“…Our findings using object-like abstract shapes are in stark contrast to the findings of Pia et al (2010) and previous work (Aniulis et al, 2016; Churches et al, 2017) using semantically unengaging geometric shapes (circle, rectangle, triangle, Rey-Osterrieth complex figures).These studies revealed consistent, and frequently significant, evidence of a leftward bisection bias. Pia et al (2010) asked participants to bisect a line drawing image of a basset-hound stretched so it resembled two parallel line stimuli with meaningful information at either end.…”
Section: Interim Discussion—experiments 1 Andcontrasting
confidence: 99%
“…Interestingly, pseudoneglect also influences representational memory 31 , whereby observers show greater accuracy when recalling landmarks that are seen in the LVF compared to the right visual field (RVF) 32 . Similarly, observers are more accurate in recalling changes in complex visual patterns when they occur in the LVF as opposed to the RVF 33 . The cheerleader effect might be modulated by the spatial arrangement of the faces in the group, because the attention of the observer is not equally distributed across the visual field, and consequently, the individual faces in the group.…”
Section: Introductionmentioning
confidence: 99%
“…As attention is biased toward the LVF 27 , 28 , 39 , we expected that distractor faces within the LVF would be more salient to the observer than those in the RVF 37 , 39 . Increased visual exploration of the LVF could facilitate ensemble coding, as observers show greater accuracy in recalling complex visual scenes viewed in the LVF compared to the RVF 33 . Furthermore, the left gaze bias might also increase the perceived attractiveness of the distractor faces when they are seen in the LVF compared to the RVF 41 , 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Another example are tasks that are believed to find pseudoneglect when participants are required to detect objects in random search arrays (for a comprehensive review, e.g., [16]) or at one or two lateral positions [1719], and with or without attentional cues ([20]; but see [21] for no lateralization effect of cueing). In addition, non-visual tasks such as perceptual judgments of tactile and auditory stimuli [3,22] as well as tests that probe mental representations and imagery ([2331]; for a review: [32]) also produce left-biased performance, opposite to what is observed in neglect in similar experiments.…”
Section: Introductionmentioning
confidence: 99%